2021
DOI: 10.22271/tpi.2021.v10.i1sc.5573
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of methicillin resistant Staphylococcus aureus (MRSA) of animal origin from Chhattisgarh

Abstract: Present investigation was made to study antibiogram profile of Methicillin Resistant Staphylococcus aureus (MRSA) of animal origin. MRSA isolates were obtained from bovine mastitis and wound infection of animals using cultural isolation and were confirmed by S. aureus specific thermonuclease (nuc) and MRSA specific mecA gene in PCR assay. A total of 13 MRSA isolates were obtained and subjected to antibiotic sensitivity test using 10 numbers of selected antibiotics by disc diffusion test. MRSA isolates exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, PCR produced the desired amplicon size of the S. aureus-specific nuc gene (270 bp) and the MRSA-specific mecA gene (533 bp). Sannat et al (2021) previously reported that these isolates were almost completely resistant to methicillin, cefoxitin and amoxicillin, but sensitive to linezolid, imipenem, clindamycin and tetracycline.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, PCR produced the desired amplicon size of the S. aureus-specific nuc gene (270 bp) and the MRSA-specific mecA gene (533 bp). Sannat et al (2021) previously reported that these isolates were almost completely resistant to methicillin, cefoxitin and amoxicillin, but sensitive to linezolid, imipenem, clindamycin and tetracycline.…”
Section: Resultsmentioning
confidence: 86%
“…Sannat et al . (2021) previously reported that these isolates were almost completely resistant to methicillin, cefoxitin and amoxicillin, but sensitive to linezolid, imipenem, clindamycin and tetracycline.…”
Section: Resultsmentioning
confidence: 92%
“…Infectious wounds are common in surgeries such as ovariosalpingohysterectomy, and this is made more problematic in the presence of multidrug-resistant bacteria, such as S. aureus . Resistance to beta-lactams is common and is often due to the presence of genes such as blaZ and mecA [ 17 ]. Therefore, herbal medicines have emerged as potential alternative antiseptics.…”
Section: Introductionmentioning
confidence: 99%